Non-steroidal anti-inflammatory drugs and biomarkers: A new paradigm in colorectal cancer - Rashid, Gowhar; Khan, Nihad Ashraf; Elsori, Deena; Rehman, Andleeb; Tanzeelah,; Ahmad, Haleema; Maryam, Humaira; Rais, Amaan; Usmani, Mohd Salik; Babker, Asaad Ma; Kamal, Mohammad Azhar; Hafez, Wael (Frontiers in Medicine, 2023)
CRC is a sporadic, hereditary, or familial based disease in its origin, caused due to diverse set of mutations in large intestinal epithelial cells. CRC is a common and deadly disease that accounts for the 4th worldwide highly variable malignancy. For the early detection of CRC, the most common predictive biomarker found endogenously are KRAS and ctDNA/cfDNA along with SEPT9 methylated DNA. Early detection and screening for CRC are necessary and multiple methods can be employed to screen and perform early diagnosis of CRC. Colonoscopy, an invasive method is most prevalent for diagnosing CRC or confirming the positive result as compared to other screening methods whereas several non-invasive techniques such as molecular analysis of breath, urine, blood, and stool can also be performed for early detection. From epidemiological and preclinical research several NSAIDs have reported chemopreventive impact on gastrointestinal malignancies, especially CRC. NSAID acts by inhibiting two cyclooxygenase enzymes, thereby preventing the synthesis of prostaglandins (PGs) and causing NSAID-induced apoptosis and growth inhibition in CRC cells. This review paper majorly focuses on the diversity of natural and synthetic biomarkers and various techniques for the early detection of CRC. An approach toward current advancement in CRC detection techniques and the role of NSAIDs in CRC chemoprevention has been explored systematically. Several prominent governing mechanisms of the anti-cancer effects of NSAIDs and their synergistic effect with statins for an effective chemopreventive measure have also been discussed in this review paper.